Onset of Exercise and Diet Program in Obese Women: Metabolic and Anorexigenic Responses Related to Weight Loss and Physical Capacities - Desgorces, F. D.; Le Page, C.; Police, C.; Neveux, N.; Cottart, C. H.; Blanc, M. C.; Raison, J.; Toussaint, J. F.; Noirez, P. (Hormone and Metabolic Research, 2015)
Perturbations of energy balance induce compensatory processes that may alter expected weight loss. In obese patients, our aim was to investigate the relationships that occurred between fasting plasma concentrations of anorexigenic peptides and metabolic parameters, appetite, physical capacity, and weight loss in the 5 first days of a program associating exercise and caloric reduction. Thirteen obese women were monitored from day 1 to day 5 with 2 exercise sessions in day 2 and day 4. We measured, in a fasted state, changes in body weight, hunger ratings, and plasma concentrations of fatty acids, triglycerides, leptin, insulin, amylin, peptide YY, and insulin-resistance index. Physical performance was assessed by a 6-min walking test. The program resulted in significantly reduced body weight (0.75±0.4 kg; p=0.001), of plasma concentrations of triglycerides, insulin, amylin, peptide YY, and the insulin-resistance index, and also increased fatty acids (p<0.05). Hunger ratings were increased (p<0.05). Program-induced changes in fatty acids, leptin, and insulin concentrations were related to physical performance (r2=0.45, 0.59, and 0.52; p<0.05, respectively) and to weight loss (r2=0.65, 0.57, 0.55; p<0.05, respectively). Five days of diet and exercise induced weight loss, improved lipid profile, and decreased insulin resistance while hunger ratings increased. Subjects with higher physical capacity lost more weight, presented higher increases in fatty acids and lower changes of leptin and insulin concentrations suggesting a better metabolic flexibility. To reduce the compensatory responses that can occur with energy imbalances, our study supports to account for individual activity level before prescribing weight-loss program associating diet and exercise.
Keywords: body weight; leptin; insulin resistance; exercise; nutrition